The Correlation of Early Initiation of Breastfeeding with Achievement of Exclusive Breastfeeding and Corresponding Factors - Marina Tamara (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To study the role of early breastfeeding in time of placental expulsion, breast milk secretion and achievement of exclusive breastfeeding. Method: A prospective cohort study was carried out at Dr. Cipto Mangukusumo General Hospital Jakarta delivery suite in January 2011. Total sample was 68 and divided into 34 sample who was conducting early initiation of breastfeeding and another 34 who did not. Time computation was conducted by the time of placental expulsion and breast milk secretion and also observation within the first 6 month to see whether exclusive breastfeeding was achieved or not. Result: From the study the obtained patients’ characteristic data were 38.2% aged 25-29 years old, 52.9% multiparity, 72.1% having middle education degree (Junior High School to Senior High School graduates), 39.7% on low economic level, and mostly unemployed (73.5%). From total sample, it was found 48 patients (70.6%) who succeded in managing exclusive breastfeeding and 20 patients (29.4%) who did not with 50% stated working as the reason. Conclusion: Early initiation of breastfeeding (EIB) has correlation with duration of placental expulsion, duration of breastmilk secretion and achievement of exclusive breastfeeding. The mean time needed to achieve early initiation of breastfeeding was 46.5 minutes. The mean time of placental expulsion in patient with EIB was 7.35 minute (SD ± 2.695) there was significant correlation between EIB with the time of placental expulsion (p=0.005). The mean time of breastmilk secretion in patient with EIB was 10.65 hours (SD ± 4.947) and there was significant correlation between EIB with the time of breastmilk secretion (p=0.000). It was found significant correlation on data analysis between patients who succeeded to manage EIB with achievement of exclusive breastfeeding (p=0.033). There is also statistically significant correlation between working mothers and achievement of exclusive breastfeeding (p= 0.005) with comparison of probability to have exclusive breastfeeding success rate between unemployed mother and employed mother. Being 1.8 times (RR: 1.800, IK 95% : 1.054-3.073) with cofounding factor is employment status. [Indones J Obstet Gynecol 2011; 35-4: 161-6] Keywords: early initiation of breastfeeding, exclusive breastfeeding, time of placental expulsion, time of breast milk secretion